Immunobiotic Lactobacillus rhamnosus improves resistance of infant mice against respiratory syncytial virus infection - Eriko, Chiba (2013)
Previously we showed that orally administered Lactobacillus rhamnosus CRL1505 beneficially regulated the balance between pro- and anti-inflammatory mediators in the lungs of poly(I:C)-challenged mice, allowing an effective inflammatory response against the TLR3/RIG-I agonist but at the same time reducing tissue damage. The aim of the present study was to investigate whether oral administration of the CRL1505 strain was able to improve resistance against respiratory syncytial virus (RSV) infection in infant mice and to evaluate the immunological mechanisms involved in the immunobiotic effect. We demonstrated that treatment of 3-week old BALB/c mice with L. rhamnosus CRL1505 significantly reduce lung viral loads and tissue injuries after the challenge with RSV. Moreover, we showed that the protective effect achieved by the CRL1505 strain is related to its capacity to differentially modulate respiratory antiviral immune response. Our results shows that IFN-γ and IL-10 secreted in response to L. rhamnosus CRL1505 oral stimulation would modulate the pulmonary innate immune microenvironment conducting to the activation of CD103+ and CD11bhigh dendritic cells and the generation of CD3+CD4+IFN-γ+ Th1 cells with the consequent attenuation of the strong and damaging Th2 reactions associated with RSV challenge. Our results indicate that modulation of the common mucosal immune system by immunobiotics could favor protective immunity against respiratory viral pathogens with a high attack rate in early infancy, such as RSV.